NKX2.1 run‐on mutation associated to familial brain–lung–thyroid syndrome. Issue 1 (29th March 2021) - Cavaliere, Elena; Gortan, Anna Jolanda; Passon, Nadia; Fabbro, Dora; Marin, Dario; Carecchio, Miryam; Baldan, Federica; Credendino, Sara Carmela; Gallo, Rosa; Cogo, Paola; Damante, Giuseppe; De Vita, Gabriella
Abstract :